2011
DOI: 10.1007/s11738-010-0688-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Arabidopsis protein S-nitrosylation in response to inoculation with Pseudomonas syringae

Abstract: Nitric oxide (NO) is a key signaling molecule in plants, being its biological effects mainly mediated through S-nitrosylation of cysteine thiols. Using the biotin switch method combined with mass spectrometry analysis we have identified 127 targets of S-nitrosylation in Arabidopsis cell suspension cultures and leaves challenged with virulent and avirulent isolates of Pseudomonas syringae pv. tomato. The NO targets are proteins associated with carbon, nitrogen, and sulpfur metabolism, photosynthesis, the cytosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 83 publications
(118 reference statements)
1
23
0
Order By: Relevance
“…Also here more intense biotin-labelling could be observed in the samples of the incompatible interaction compared to the compatible interaction. And it correlated with the higher amount of proteins purified in the case of the incompatible interaction [61].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Also here more intense biotin-labelling could be observed in the samples of the incompatible interaction compared to the compatible interaction. And it correlated with the higher amount of proteins purified in the case of the incompatible interaction [61].…”
Section: Discussionmentioning
confidence: 84%
“…These candidates are categorized to diverse classes such as signalling and stress-related proteins, or metabolic enzymes. 127 candidate proteins were identified in Arabidopsis leaves and cell extracts treated with virulent and avirulent P. syringae [15]. More than 60% of these candidates have been identified for the first time as NO targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This PTM is believed to impact protein conformation, function, and/or location. The biotin switch technique (BST) or related approaches have been used to identify the S -nitrosylated proteins in all plant cellular compartments, indicating the extent and importance of regulatory mechanism by which NO modulates protein functions and cell signaling in the plant life cycle [83,84,85,86,87,88,89,90,91,92,93]. Several studies have shown that NO affects seed dormancy, germination, and sensitivity of seeds towards abscisic acid (ABA) [94,95].…”
Section: Post-translational Modifications Of Mitochondrial Proteinmentioning
confidence: 99%
“…As a subunit in the pyruvate dehydrogenase complex, DHLD is involved in converting pyruvate to acetyl-CoA and has been implemented in increasing lipid production by providing additional lipid precursors (acetyl-CoA) in Chlorella protothecoides grown heterotrophically on sugarcane bagasse hydrolyzate (Mu et al, 2015). DHLD has also been shown to be S -nitrosylated in plants responding to pathogens, cold, and abiotic stress (Maldonado-Alconada et al, 2011; Ortega-Galisteo et al, 2012; Puyaubert et al, 2014). As with biotin carboxylase, DHLD is only S -nitrosylated during nitrogen-replete growth and represents another potential target for protein engineering to eliminate the negative effects of S-nitrosylation on this enzyme.…”
mentioning
confidence: 99%